Identification of Digital Literacy Skills on Critical Thinking of Physics Education Students - Afifah Mufidah; Putranta, Himawan (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2024)
Digital literacy is one of the skills that students must master to prepare themselves to face challenges in the era of society 5.0. This research aims to identify the digital literacy abilities of physics education students and their relationship with critical thinking abilities. Data is collected from students through a quantitative approach, using questionnaires and statistical analysis. This research uses a simple random sampling technique in which all students have the opportunity to become samples for this research. This is because this research does not have any restrictions, so everyone has the opportunity to become a respondent. Respondents consisted of 57 physics education students at UIN Sunan Kalijaga Yogyakarta. The research results show that there is a positive relationship between digital literacy and critical thinking skills. Students who have good digital literacy tend to show higher critical thinking skills. This research also identifies factors that influence digital literacy, such as access to technology, understanding of digital information, and skills in evaluating information sources. These findings are expected to provide insight into the development of a physics education curriculum that is more effective in improving students' critical thinking skills through digital literacy.